A micropatterning approach for imaging dynamic Cx43 trafficking to cell–cell borders. Issue 8 (17th January 2014) - Zhang, Shan-Shan; Hong, SoonGweon; Kléber, André G.; Lee, Luke P.; Shaw, Robin M.
Abstract : The precise expression and timely delivery of connexin 43 (Cx43) proteins to form gap junctions are essential for electrical coupling of cardiomyocytes. Growing evidence supports a cytoskeletal‐based trafficking paradigm for Cx43 delivery directly to adherens junctions at the intercalated disc. A limitation of Cx43 localization assays in cultured cells, in which cell–cell contacts are essential, is the inability to control for cell geometry or reproducibly generate contact points. Here we present a micropatterned cell pairing system well suited for live microscopy to examine how the microtubule and actin cytoskeleton confer specificity to Cx43 trafficking to precisely defined cell–cell junctions. This system can be adapted for other cell types and used to study dynamic intracellular movements of other proteins important for cell–cell communication. Abstract : A micropatterning technique to constrain cell pair geometry and contact points. HeLa and cardiomyocyte pairs express N‐cadherin and Cx43 at cell–cell junctions. The cytoskeletal delivery machinery for Cx43 orients to the cell–cell border. Micropatterning allows controlled analysis of real‐time Cx43 trafficking from the Golgi to the cell border.